Automated Patch Clamp Analysis of nAChα7 and NaV1.7 Channels. Issue 1 (16th June 2014) - Obergrussberger, Alison; Haarmann, Claudia; Rinke, Ilka; Becker, Nadine; Guinot, David; Brueggemann, Andrea; Stoelzle‐Feix, Sonja; George, Michael; Fertig, Niels
Abstract: Automated patch clamp devices are now commonly used for studying ion channels. A useful modification of this approach is the replacement of the glass pipet with a thin planar glass layer with a small hole in the middle. Planar patch clamp devices, such as the three described in this unit, are overtaking glass pipets in popularity because they increase throughput, are easier to use, provide for the acquisition of high‐quality and information‐rich data, and allow for rapid perfusion and temperature control. Covered in this unit are two challenging targets in drug discovery: voltage‐gated sodium subtype 1.7 (NaV 1.7) and nicotinic acetylcholine α7 receptors (nAChα7R). Provided herein are protocols for recording activation and inactivation kinetics of NaV 1.7, and activation and allosteric modulation of nAChα7R. Curr. Protoc. Pharmacol . 65:11.13.1‐11.13.48. © 2014 by John Wiley & Sons, Inc.